Uma avaliação sob a perspectiva antropológica da política de educação de jovens e adultos (EJA) em Maracanaú (CE) - Silva, Francisco Aderlan Ferreira da (2024)
Adult and Youth Education (EJA) is one of the most significant forms of educational inclusion, providing learning opportunities for those who, for various reasons, could not access formal education at the regular age. It stands as one of the fundamental educational policies for promoting social inclusion and combating educational exclusion across Brazil. In Maracanaú, Ceará, the implementation of EJA plays a central role in the pursuit of democratizing access to education. Therefore, the dissertation's general objective was to evaluate how EJA public policies are perceived and assessed by different stakeholders in Maracanaú, exploring their implementation, results, potentialities, and limitations. To achieve this, the study employed an in-depth evaluation approach, using the analytical frameworks of Rodrigues (2008) and the hermeneutic paradigm of Lejano (2012) for a multidimensional assessment. Methodologically, the investigation adopted an anthropological perspective, using fieldwork to capture the perceptions of managers, educators, and primary beneficiaries of the policies. This approach is based on the contributions of Gussi (2014 and 2017) and Gussi and Oliveira (2016). The study is qualitative in nature. Initial data were collected through bibliographic and documentary review, followed by participant observation, semi-structured interviews, and life histories. One school from each administrative territory was selected, totaling nineteen participants. The results indicate that the political context in Brazil significantly influenced the development and implementation of EJA policy, with each administration bringing its own perspectives and priorities. Despite the challenges, EJA has promoted the emancipation and formation of critical and participatory citizens. The study highlights the importance of teacher training and the integration with the sociocultural profile of students for a more effective educational practice. Additionally, future research should focus on teachers' working conditions, infrastructure, teaching materials, and community involvement. It concludes that it is necessary to improve policies to better serve the EJA audience, promote social inclusion, and enhance the quality of education. The findings of this study aim to contribute significantly to the development of more appropriate strategies in the educational field.